Harmony of Spirituality and Professionalism: Behavioral Accounting in the Perspective of Tri Hita Karana - Prameswari, Ida Ayu Nirma; Dewi, Ni Made Sintya Surya; Sari, Desak Made Mya Yudia (Islamic Accounting Journal, 2026)
Objective & object: This research aims to understand how the cultural philosophy of Tri Hita Karana (THK) is implemented in shaping professional behavior and work ethics at BCR Consulting, a tax consulting firm in Denpasar, Bali. The object of this study focuses on the application of the values of Parahyangan, Pawongan, and Palemahan within the organization's activities during the 2025 research period. Methods: This study employed a qualitative approach to gain an in-depth understanding of the implementation of Tri Hita Karana values and their relationship with professionalism in the context of behavioral accounting at BCR Consulting. Data were collected through in-depth interviews, document studies, and literature reviews, involving eight informants, comprising one leader and seven employees. Data analysis was conducted through the established qualitative process of data reduction, data display, and conclusion drawing. Results & Conclusions: The research demonstrates that Tri Hita Karana values are genuinely and thoroughly integrated into the company’s work culture. Parahyangan fosters spiritual awareness and moral integrity; Pawongan strengthens social relationships and teamwork; and Palemahan cultivates a harmonious and productive work environment. Collectively, these three elements establish a critical balance between technical professionalism and ethical responsibility. Limitations: This research is confined to a single location and a limited number of informants, which means the findings cannot be broadly generalized. Implications: The results provide a valuable direction for developing an ethical and professional behavior system rooted in local cultural values. Furthermore, these findings serve as a foundation for future research concerning the interplay between spirituality and behavioral accounting